Bees of the genera Dufourea and Dieunomia of Michigan (Hymenoptera: Apoidea: Halictidae), with a key to the Dufourea of the eastern United States - Gibbs, Jason; Dumesh, Sheila; Griswold, Terry L. (Journal of Melittology, 2014)
The halictid bees of the genera Dufourea Lepeletier de Saint Fargeau (Rophitinae) and Dieunomia Cockerell (Nomiinae) occurring in Michigan are reviewed. Two new records for Michigan are provided: Dufourea harveyi (Cockerell), new status, and Dieunomia heteropoda (Say). This is also the first published record of D. harveyi in the eastern United States. The occurrence of Dieunomia in southwest Michigan is the first record of the subfamily Nomiinae for the state. Information on the biology and distribution of each species is summarized. An identification key to the Dufourea of the eastern United States is provided.